2012
DOI: 10.1121/1.3693644
|View full text |Cite
|
Sign up to set email alerts
|

Perception of urban park soundscape

Abstract: A number of studies have been initiated to explore how to improve the soundscape quality in urban parks. However, good soundscape quality in parks cannot be provided without a thorough understanding of the complex relationships among sound, environment, and individuals. As acoustic comfort is considered to be an important outcome of soundscape quality, this study investigates the relative impacts of the factors influencing acoustic comfort evaluation by formulating a multivariate ordered logit model. This stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
0
8

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(58 citation statements)
references
References 27 publications
3
47
0
8
Order By: Relevance
“…While a number of useful conclusions have been made regarding the audiovisual environment of rural landscapes, [6][7][8][9][10][11] there is still a lack of studies exploring the visual attention of rural landscapes in tranquility evaluations while considering different sounds. In this research, therefore, the visual attention of landscapes in tranquility evaluations with and without sound stimuli is examined by carrying out eye tracking experiments using Tobii T60XL Eye Tracking equipment-an objective recorder of human eye movement characteristics when dealing with visual information, based on landscape field pictures and sounds collected from typical villages in China, which are undergoing rapid urbanization.…”
Section: -5mentioning
confidence: 99%
“…While a number of useful conclusions have been made regarding the audiovisual environment of rural landscapes, [6][7][8][9][10][11] there is still a lack of studies exploring the visual attention of rural landscapes in tranquility evaluations while considering different sounds. In this research, therefore, the visual attention of landscapes in tranquility evaluations with and without sound stimuli is examined by carrying out eye tracking experiments using Tobii T60XL Eye Tracking equipment-an objective recorder of human eye movement characteristics when dealing with visual information, based on landscape field pictures and sounds collected from typical villages in China, which are undergoing rapid urbanization.…”
Section: -5mentioning
confidence: 99%
“…More significantly age plays a greater role in sound perception. The same study showed that younger people (10)(11)(12)(13)(14)(15)(16)(17) year olds) are less tolerant of sounds relating to nature whereas older people are more likely to prefer soundscapes where natural sounds occur. In a similar study by the same authors [9], cultural background and environmental experience play an important role in people's judgement of sound preference.…”
Section: Introductionmentioning
confidence: 78%
“…It is widely regarded that tranquil areas and open public spaces can lead to comfort and can make people perceivably sense a quieter environment whereby to provide a comfortable acoustic environment the background level must be reduced in open urban spaces [16,17]. Furthermore, the density of urban spaces can influence soundscape perception in a negative way [8].…”
Section: Introductionmentioning
confidence: 98%
“…[14] Some of them investigated the different types of vegetation that helped attenuate noise exposure, [15] while others focused on the phenomenon of "soundscape." [16][17][18][19] The ultimate goal of noise control is to promote relaxation, satisfaction and well-being in urban residents. [9] As noise reduction on acoustical level greatly depends on the characteristics of vegetation and the design of urban green spaces the exploitation of the psychological role of vegetation as a noise buffer is much preferable.…”
Section: Introductionmentioning
confidence: 99%